The maximum effect of deep lakes on temperature profiles – determination of the geothermal gradient (2009)
Understanding the climate change processes on the basis of geothermal observations in boreholes is an important and at the same time high-intricate problem. Many non-climatic effects could cause changes in ground surface temperatures. In this study we investigate the effects of deep lakes on the borehole temperature profilesobserved within or in the vicinity of the lakes. We propose a method based on utilization of Laplace equation with nonuniform boundary conditions. The proposed method makes possible to estimate the maximum effect of deep lakes (here the term "deep lake" means that long term mean annual temperature of bottom sediments can beconsidered as a constant value) on the borehole temperature profiles. This method also allows one to estimate an accuracy of the determination of the geothermal gradient.